Leadership and authority in China, 1895-1976 - Sullivan, Lawrence R. (Lexington Books, 2012)
Leadership and Authority in China examines the ""constitutional"" conflict in the Chinese Communist Party (CCP) and Chinese society over two diametrically opposed concepts of leadership and authority. Behind the façade of political and ideological unity lay a titanic struggle between a model of institutional authority and "collective leadership" drawn from the strong anti-despotic impulse in modern Chinese thought versus a neo-traditional ""leader principle"" of charismatic authority centered on the "Great Helmsman" Mao Zedong that ul.